Membrane Distillation - Enrico Drioli (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Membrane distillation (MD) is a relatively new thermal membrane process which is attracting significant interest as a potential low cost and energy saving alternative to conventional separation processes such as distillation and reverse osmosis (RO). Its main advantages are the possibility to exploit waste grade heat and low grade heat for operation, and the production of high-purity distillate which is almost independent of feed concentration. Other benefits include the theoretically complete rejection of non-volatile solutes, the relative operating pressure and membrane-fouling problem. On the contrary, wetting and temperature polarization are its main drawbacks. The Special Issue covers developments at various forefronts of MD, including membrane preparation, fouling and scaling issues, process improvements and applications.